X-ray vascular technologies. analysis of errors in the diagnostic and treatment algorithm of patients with mediastinum tumors - Kravchenko, Roman; Avdosiev , Yuriy (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
This article considers the unsolved problem of diagnostic and therapeutic approach to patients with mediastinal tumors. The aim of the study was to increase the efficacy of treatment of patients with mediastinal epithelial tumors by using intra-arterial chemoembolization as a neoadjuvant therapy to create ischemia and high concentrations of cytostatics in tumors over a long period of time to devitalize tumor tissue and reduce overall chemotherapy toxicity. Object of study. Epithelial tumors of the thymus gland. Research methods: Clinical, laboratory, morphological, instrumental, statistical. Laboratory tests will include general clinical blood tests, biochemical parameters (ALT, AST, bilirubin, alkaline phosphatase, gamma-glutamine transpeptidase, lactate dehydrogenase, albumin), biochemical markers of thymus tumor (AFP, HGT), acetyl. General blood test (hemoglobin, erythrocytes, leukocytes, platelets). Instrumental methods of examination will include CT (computed tomography) with intravenous contrast, MRI (magnetic resonance imaging). Conclusions can be drawn from the literature. It can be stated that there is no single point of view on the diagnosis and choice of treatment tactics for patients with epithelial tumors of the thymus. Histological heterogeneity of tumors of this anatomical region with the similarity of clinical manifestations and radiological symptoms requires the development of algorithms for their differential diagnosis and optimization of treatment. In addition, over the last decade in Ukraine there has been a significant increase in the number of mediastinal tumors, especially thymus. Given mainly the young age of patients with this disease and the high degree of aggressiveness of the disease, the problem is transformed at the social level. It is also necessary to reconsider the traditional approach to the treatment of this pathology, the first link of which is considered to be surgery.